VIC maternity services lead push for gender equality: New training available - Thomas, Anita (My University, 2022)
Public antenatal and maternity services across Victoria have demonstrated their commitment to building gender equality in their local communities by taking part in health Ability's Applying a Gender Equality Lens to Childbirth and Parenting Education training. The training is an integral component of the Strengthening Gender Equality in Antenatal and Maternity Services project.
Australian Midwifery News
Keywords: Gender